Disproportionation and Ligand Lability in Low Oxidation State Boryl‐Tin Chemistry. Issue 10 (4th January 2023) - Zheng, Xiongfei; Crumpton, Agamemnon E.; Protchenko, Andrey V.; Heilmann, Andreas; Ellwanger, Mathias A.; Aldridge, Simon
Abstract: Boryltin compounds featuring the metal in the+1 or 0 oxidation states can be synthesized from the carbene‐stabilized tin(II) bromide (boryl)Sn(NHC)Br (boryl=B(NDippCH)2 ; NHC=C(N i PrCMe)2 ) by the use of strong reducing agents. The formation of the mono‐carbene stabilized distannyne and donor‐free distannide systems (boryl)SnSn(IPrMe)(boryl) (2 ) and K2 [Sn2 (boryl)2 ] (3 ), using Mg(I) and K reducing agents mirrors related germanium chemistry. In contrast to their lighter congeners, however, systems of the type [Sn(boryl)] n are unstable with respect to disproportionation. Carbene abstraction from 2 using BPh3, and two‐electron oxidation of 3 both result in the formation of a 2 : 1 mixture of the Sn(II) compound Sn(boryl)2, and the hexatin cluster, Sn6 (boryl)4 (4 ). A viable mechanism for this rearrangement is shown by quantum chemical studies to involve a vinylidene intermediate (analogous to the isolable germanium compound, (boryl)2 Ge=Ge), which undergoes facile atom transfer to generate Sn(boryl)2 and trinuclear [Sn3 (boryl)2 ]. The latter then dimerizes to give the observed hexametallic product 4, with independent studies showing that similar trigermanium species aggregate in analogous fashion. Abstract : The carbene‐stabilized distannyne and donor‐free distannide systems (boryl)SnSn(IPrMe)(boryl) and K2 [Sn2 (boryl)2 ], can be synthesized from (boryl)Sn(NHC)Br using Mg(I) or K reducing agents. In contrast to their germanium congeners, systems of the type [Sn(boryl)] n are unstable with respect to disproportionation: NHC abstraction from (boryl)SnSn(IPrMe)(boryl) and 2‐electron oxidation of K2 [Sn2 (boryl)2 ] both yield a 2 : 1 mixture of Sn(boryl)2 and the hexatin cluster, Sn6 (boryl)4 . A viable mechanism for this rearrangement is shown by quantum chemical studies to involve the vinylidene‐type intermediate (boryl)2 Sn=Sn.